Molecular dissection of the valproic acid effects on glioma cells - Hoja, Sabine (Oncotarget, 2016)
Many glioblastoma patients suffer from seizures why they are treated with antiepileptic agents. Valproic acid (VPA) is a histone deacetylase inhibitor that apart from its anticonvulsive effects in some retrospective studies has been suggested to lead to a superior outcome of glioblastoma patients. However, the exact molecular effects of VPA treatment on glioblastoma cells have not yet been deciphered. We treated glioblastoma cells with VPA, recorded the functional effects of this treatment and performed a global and unbiased next generation sequencing study on the chromatin (ChIP) and RNA level. 1) VPA treatment clearly sensitized glioma cells to temozolomide: A protruding VPA-induced molecular feature in this context was the transcriptional upregulation/reexpression of numerous solute carrier (SLC) transporters that was also reflected by euchromatinization on the histone level and a reexpression of SLC transporters in human biopsy samples after VPA treatment. DNA repair genes were adversely reduced. 2) VPA treatment, however, also reduced cell proliferation in temozolomide-naive cells: On the molecular level in this context we observed a transcriptional upregulation/reexpression and euchromatinization of several glioblastoma relevant tumor suppressor genes and a reduction of stemness markers, while transcriptional subtype classification (mesenchymal/proneural) remained unaltered. Taken together, these findings argue for both temozolomide-dependent and -independent effects of VPA. VPA might increase the uptake of temozolomide and simultaneously lead to a less malignant glioblastoma phenotype. From a mere molecular perspective these findings might indicate a surplus value of VPA in glioblastoma therapy and could therefore contribute an additional ratio for clinical decision making.